Financial inclusion, environmental technology, and sustainable environment in China: evidence from an N-shaped EKC - Sun, Wei; Li, Qiang; Uddin, Ijaz (Frontiers in Environmental Science, 2025)
Financial inclusion (FI) and technological innovation (TI) are pivotal in advancing SDG 13 (Climate Action) by enabling access to sustainable solutions and promoting low-carbon technologies. FI allows marginalized communities and businesses to invest in renewable energy (RE) and energy-efficient technologies, while TI drives the development of clean energy solutions and CO2 emissions (CO2E) reducing innovations. Together, they empower societies to take significant action against climate change, fostering a global transition to a low-carbon economy and helping achieve the targets of SDG 13. Previous studies have focused exclusively on the impact of either FI or TI on CO2E in China under the N-shaped Environmental Kuznets Curve (EKC). To address this gap, the current study examines the combined effects of FI and TI on CO2E within the EKC framework for the Chinese economy. This study utilizes the Autoregressive Distributed lag (ARDL), fully Modified ordinary least square (FMOLS), and Dynamic ordinary least square (DOLS) methods by using the time series quarterly data from 2006Q1 to 2022Q4. The ARDL long-run and short-run results confirm that there is an inverted N-shaped EKC between GDP and CO2E. While FI, TI, and RE have negative effects on CO2E. This study has several policy recommendations for policymakers to promote environmental sustainability in China.